The difficulties that mathematics teachers face in applying modern teaching strategies in the intermediate stage: a field study in Constantine middles schools - Nameche, Fatima; Boumengar, Mourad (Journal of Human Sciences, 2023)
This study aimed to know the difficulties encountered by teachers of mathematics in the application of modern teaching strategies and if there are statistically significant differences in these difficulties due to gender variables - seniority and style of training. In order to verify the study hypotheses, we relied on the descriptive analytical approach by constructing a questionnaire as a study tool that was applied to an intentional sample of (58) middle-stage mathematics teachers, after verification of the psychometric properties of the study tool. The data was analyzed using frequencies, percentages, arithmetic means, Mann-Wattney test, Croxall-Wallis test. The study concluded that teachers of mathematics encounter various difficulties in applying modern teaching strategies, as it was found that there are statistically significant differences in the research sample’s tendencies towards difficulties ( gender-age), and there are statistically significant differences attributed to the variable These findings constitute a set of suggestions and recommendations.